TEACHING DEMOGRAPHY THROUGH BLENDED LEARNING (DEGREE IN LABOUR RELATION AND HUMAN RESOURCES) - Huete-Morales, M. Dolores; Aguilera-Morillo, M. Carmen; Vargas-Jimenez, Maravillas; Garcia-Lopez, Pedro A.; Sanchez-Borrego, Ismael; Quesada-Rubio, J. Manuel; Marmolejo-Martin, Juan A.; Carrillo-Ballesteros, Belen (European Scientific Journal, ESJ, 2014)
The current teaching climate, in the framework of the European Higher Education Area, is favourable to the design of tools allowing students to self-study, following course subjects independently of their teachers and of the classroom. The study of demographic statistics, in particular, can thus be enhanced for undergraduates enrolled in courses involving this subject, such as labour sciences. Demographic statistics is an appropriate area in which to apply new technologies, as all the practical information used is located on the websites of the various Institutes of Statistics. Very little software has been designed for the application of the techniques associated with this discipline, and so there is a real need for this type of selflearning tool.